PEMBUATAN APLIKASI PERMAINAN SEBAGAI MEDIA PEMBELAJARAN DI SEKOLAH LUAR BIASA AUTIS - Bagas Satya Dian Nugraha; Galih Putra Riatma; Satrio Binusa Suryadi; Muhammad Unggul Pamenang; Adevian Fairuz Pratama; Arief Prasetyo (P3M Politeknik Negeri Malang, 2025)
SLB Autis Laboratorium UM is a school that is specifically designed to educate students with disabilities, especially autism. In the learning process, teachers often face difficulties in providing effective learning materials. This ineffectiveness is caused because the material delivered is dominated by text and verbal explanations, where students are less able to digest the information delivered using this method. Based on the results of partner observations, students tend to be more receptive to information in audio-visual form. The use of creative learning media in the form of game applications is considered to be able to provide a solution to this problem. Therefore, an educational game was designed which is expected to help improve the quality of learning and create a more interesting learning experience.